Extracts from red eggplant: impact of ohmic heating and different extraction solvents on the chemical profile and bioactivity - Santos, Pedro Miguel Ferreira (2021)
The Supplementary Material for this article can be found online at: https://www.frontiersin.org/articles/10.3389/fsufs.2021.804004/full#supplementary-material